2016
DOI: 10.1016/j.ypmed.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of active commuting with body mass index

Abstract: ObjectiveTo investigate the longitudinal associations between active commuting (walking and cycling to work) and body mass index (BMI).MethodWe used self-reported data on height, weight and active commuting from the Commuting and Health in Cambridge study (2009 to 2012; n = 809). We used linear regression to test the associations between: a) maintenance of active commuting over one year and BMI at the end of that year; and b) change in weekly time spent in active commuting and change in BMI over one year.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 45 publications
3
42
1
Order By: Relevance
“…Equally those who transitioned from active to car commuting reported a significant increase in BMI. Mytton and colleagues 11 used two waves of data from the Commuting in Cambridge study to demonstrate that maintenance of cycle commuting was associated with lower BMI when compared with maintenance of sedentary commuting. However corroborative results were not found for walking 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally those who transitioned from active to car commuting reported a significant increase in BMI. Mytton and colleagues 11 used two waves of data from the Commuting in Cambridge study to demonstrate that maintenance of cycle commuting was associated with lower BMI when compared with maintenance of sedentary commuting. However corroborative results were not found for walking 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Mytton and colleagues 11 used two waves of data from the Commuting in Cambridge study to demonstrate that maintenance of cycle commuting was associated with lower BMI when compared with maintenance of sedentary commuting. However corroborative results were not found for walking 11 . The protective effects of cycle commuting have also been reported for schoolchildren 12 .…”
Section: Introductionmentioning
confidence: 99%
“…DM was not associated with OA in either gender in this study. Overweight status has been shown to be strongly associated with OA, and physical activity tends to lower BMI [29,30]. Therefore, the fact that the green and blue collar occupations involved higher levels of physical activity may have influenced the results of this study.…”
Section: Discussionmentioning
confidence: 96%
“…Data from the Nurses' Health Study showed a 16-year association of increase in walking and cycling with lower weight gain over time in premenopausal women [28], while another recent 3-year longitudinal study did not find such association [29]. In a nationally representative survey of UK residents (n = 12,796), Laverty et al [30] found negative associations for walking and cycling to work (assessed separately) with both BMI and likelihood of overweight or obesity.…”
Section: Discussionmentioning
confidence: 99%